Urban health in India: from smaller steps to a big leap - Smita Shrivastava; Ashutosh Kothari; Himanshu Bhushan (International Society of Global Health, 2023)
The focus on urban health in India was majorly lagging in the initial years post-independence except in some specific areas like family planning during the 1st and 2nd Five Year Plans (FYPs). The subsequent FYPs too for the next ten to fifteen years did not witness any shift in focus to the diverse health-related problems in urban areas. The National Rural Health Mission in 2005 had a primary focus on rural health, with some initiatives taken up to expand health services in urban areas. However, the major milestone in urban health was the launch of the National Urban Health Mission (NUHM) in 2013, wherein urban health in India got centre stage. The COVID-19 pandemic led to an accelerated response in strengthening the health systems across the country including health infrastructure in urban areas. Overall, it can be said that urban health in the country is currently undergoing major transitions. Despite there being several issues, the reforms for assured comprehensive primary health care services seem promising in improving the status of health in urban India. Convergence with key stakeholders and other sectors beyond health would be the key to bridging the gap in addressing social determinants of health, social protection for migrants and floating population and focusing on environmental protection. Such actions would leverage enhanced health access of urban poor to quality and equitable healthcare services. The paper focuses on government policies that began prioritising urban health, the limitations of present health systems, and the roadmap to construct a much-needed future foundation for improved health outcomes in urban India.